Respuesta :
Answer:
Step-by-step explanation:
using distance formula:
distance between two points =[tex]\sqrt{(-2-(-5))^{2} +(3-1)^{2} }[/tex]
=whole root of (-2+5)^2+2^2
=whole root of 3^2+2^2
=whole root of 9+4
=[tex]\sqrt{13}[/tex] units =3.60555... #answerwithquality #BAL
Answer:the distance between the two points is 3.61
Step-by-step explanation:
The formula for determining the distance between two points is expressed as
d = √(x2 - x1)^2 + (y2 - y1)^2
From the information given,
y2 = 3
y1 = 1
x2 = - 2
x1 = - 5
Therefore, the distance between the two points would be
d = √(-2 - -5)^2 + (3 - 1)^2
d = √3^2 + 2^2
d = √9 + 4
d = √13 = 3.61